Development of a Duplex Insulated Isothermal PCR Assay for Rapid On-Site Detection and Differentiation of Genotypes 1 and 2 of African Swine Fever Virus - Song, Ruilong; Liu, Penggang; Yang, Yang; Lee, Hu Suk; Chen, Changhai; Wu, Xiaodong; Li, Xiangdong (Frontiers in Cellular and Infection Microbiology, 2022)
Genotype II African swine fever virus (ASFV) has been plaguing Asian pig industry since 2018. Recently, genotype I ASFV was reported for the first time in China. Since there is no commercial vaccine available against ASFV, early onsite detection and quick culling procedures are commonly used by many countries all over the world. It is desirable that the above two genotypes of ASFV could be quickly differentiated during onsite detection at the same time. In this study, we established a sensitive and simple Fluorescent Probe Hydrolysis-Insulated isothermal PCR (iiPCR) that can detect and differentiate two genotypes of ASFV within 40 minutes. The positive or negative results of tested samples displayed on the screen of device automatically after PCR amplification was complete. The detection limit of the iiPCR was tested to be 20 copies for both genotype I and genotype II ASFVs. There was no cross-reactivity with other swine viruses by using the established iiPCR. Fifty-eight ASFV positive samples confirmed by National ASF Reference Laboratory were subjected to the established duplex iiPCR for genotype differentiation. The results showed that all these ASFV-positive samples belong to genotype II. At last, we found serum samples could be directly used as the templates for iiPCR without comprising sensitivity and specificity. Therefore, the duplex iiPCR established in study provide a useful tool for ASFV onsite detection and genotype differentiation.